Model Pengembangan Pembiayaan Syariah Sektor Pertanian di Provinsi Aceh: Suatu Telaah Soft System Methodology - Hafiizh Maulana; Abrar Amri; Nurul Iski (Jurnal Ilmu Pertanian Indonesia, 2023)
The agricultural sector is the largest sector for economic output in Aceh which also dominates the largest number of workers in Aceh. The Aceh government needs to establish strategic steps to formulate financing in the sector as stipulated in the agricultural regulations based on Qanun Number 11 of 2018 about Islamic Financial Institutions (LKS). This research is designed to formulate system for developing Islamic financing in the agricultural sector after the implementation of Qanun Number 11 of 2018 about LKS in Aceh with soft systems methodology (SSM) approach. This study has resulted a conceptual model of the Islamic financing strategy for the agricultural sector in Aceh Province. Based on the results of the review of the conceptual framework using the SSM approach, strategies that can be performed for implementation of Islamic agricultural finance are the Islamic financial product strategy, Islamic agricultural financing institutional strategy, local and central government communication strategies, and human resource development strategy. This study recommends that the Government of Aceh needs to prepare regulatory policies, Islamic financial product schemes, and institutions in strengthening the implementation of Islamic financing based on the agricultural sector in Aceh. Keywords: islamic financing, agriculture, soft systems methodology, Qanun LKS